Compare the E?ects of Dexmedetomidine Infusion versus Normal Saline as Placebo on Haemodynamic Response in Elective Laparoscopic Surgery Under General Anaesthesia - Sankar, V. Ravi; T. Jamuna; B. Raju (Academia Anesthesiologica International, 2020)
Background: Throughout the present medical age, laparoscopic surgery is the most effective diagnostic and therapeutic methods. But it is associated with potentially harmful neuroendocrine response. Subjects and Methods: In our study we used dexmedetomidine infusion in group D and normal saline at a rate of 0.4mcg / kg / hr as placebo in group N beginning from 10 minutes before induction before pneumoperitoneum release. Patients in both groups were alike in age, gender, BMI, grade of ASA and anaesthesia. Results: After 10 min infusion of dexmedetomidine and normal saline in group D and group N respectively, fall in HR, DBP and Mean arterial pressure was significantly increased in group D compared to group N. Difference found in both the groups was statistically significant. Group N showed significant increase in HR, SBP, DBP and MAP during laryngoscopy, intubation and at 2 min , 5 min and 10 min after creation of pneumoperitoneum. Difference found was statistically significant in both groups. Thus attenuation in HR, SBP, DBP and MAP was seen in group D as compared to group N during laryngoscopy, tracheal intubation and pneumoperitoneum which were statistically significant. Group N showed statically significant increase in HR, DBP and MAP during extubation compared to group D. Difference found in both the groups was statistically significant. Thus attenuation in HR, DBP and MAP was seen in group D as compared to group N during extubation which was statistically significant. Postoperative sedation score was more in group D compared to group N which was statistically significant. Post-extubation, rescue analgesia was required early in group N compared to group D. Adverse effect in form of bradycardia was seen in 2 patients in group D which did not require atropine administration. Conclusion: Dexmedetomidine infusion at a rate of 0.4 mcg / kg / hr apparently started 10 minutes before the induction of anesthesia before release of pneumoperitoneum without any bolus dose. Useful adjuvant anesthesia to diminish the response of haemodynamic stress to intubation, Pneumoperitoneum, and extubation in laparoscopic surgical patients.